The Effects of Customer Trust, Service Quality, And Customer Experience on Customer Loyalty at Kintamani Jeep Tour - Nyoman Yusita; Ni Wayan Eka Mitariani; I Putu Wahyu Dwinata JS (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Customer loyalty is a critical factor to consider. A company’s success is determined by its ability to build customer loyalty. This study aims to examine the influence of customer trust, service quality, and customer experience on customer loyalty at Kintamani Jeep Tour. The study was conducted at Kintamani Jeep Tour via an online survey targeting the company’s active Instagram followers. The sample for this study consisted of 90 individuals who had used Kintamani Jeep Tour’s services at least twice. The sampling technique employed in this study was purposive sampling, with data collection conducted through observation, interviews, questionnaires, and documentation. The data analysis technique used in this study was linear regression analysis using SPSS version 26. Based on the analysis results, this study indicates that customer trust has a positive and significant effect on customer loyalty toward Kintamani Jeep Tour. This means that the higher the customer trust, the greater the customer loyalty toward Kintamani Jeep Tour. Service quality has a positive and significant effect on customer loyalty toward Kintamani Jeep Tour. This implies that the better the service quality, the higher the customer loyalty toward Kintamani Jeep Tour will be. Customer experience has a positive and significant effect on customer loyalty toward Kintamani Jeep Tour. This implies that the better the customer experience, the higher the customer loyalty toward Kintamani Jeep Tour will be.